Assessment of personality traits and skills of UPILS and non-ILS students as indicator of a career in information brokering - Moraña, Mark F. (2002)
Information brokering lies on the concept of information as commodity. An information broker searches for raw data that will solve a well-defined problem, packages the information into a usable form and delivers it to the client for a fee. An information broker is a reference librarian let loose. Thus, an information broker should possess the personality traits and skills of an entrepreneur and a librarian at the same time